The effect of supply chain power on bank financing - Rahaman, Mohammad M.; Rau, P. Raghavendra; Zaman, Ashraf Al (Journal of Banking & Finance, 2020)
Using comprehensive bank-loan contract information, we show that the power of a firm relative to its suppliers eases its terms of bank financing, specifically through lower loan prices and less restrictive non-price contract terms. Our results are robust to controlling for product-market competition. Supply chain power enables the firm to achieve a greater level of control over its inventory, constituting a significant portion of the reduction in its overall loan cost. We argue that it is important to consider supply-chain related issues when analyzing the external-financing capacity of firms.